2022
DOI: 10.1101/2022.03.22.485313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenology of plant reproduction, foliar infection, and herbivory change along an urbanization gradient

Abstract: Urbanization is associated with numerous environmental changes that may affect the timing of plant reproduction and foliar damage by pathogens, herbivores, and human activities. Yet such effects have not previously been quantified simultaneously in plant populations across levels of urbanization. Thus, it remains unclear how urbanization impacts multiple fitness components of a single plant species. Moreover, it is unclear which effects are consistent between species. We studied 22 populations of two co-occuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It has been reported that abiotic conditions associated with climate change can either induce or delay developmental processes and flowering in a genotype-dependent manner [43][44][45][46]. Flowering has been also described to be altered by the result of human activities such as urbanization [47,48] or biodiversity loss [49]. These changes in plant development will result in viruses facing host populations with altered levels of susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that abiotic conditions associated with climate change can either induce or delay developmental processes and flowering in a genotype-dependent manner [43][44][45][46]. Flowering has been also described to be altered by the result of human activities such as urbanization [47,48] or biodiversity loss [49]. These changes in plant development will result in viruses facing host populations with altered levels of susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Data (Fox et al, 2024a) are available in Dryad at https:// doi.org/10.5061/dryad.wpzgmsbrn. Code (Fox et al, 2024b) is available at Zenodo at https://doi.org/10.5281/ zenodo.7458687.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%